Takhrij and Syarah Hadith of Agrotechnology: The Study of Date Palm Cultivation in Terms of Economic and Ecological Aspects in Indonesia - Siti Nurhalimah; Wahyudin Darmalaksana; Esty Puri Utami (UIN Sunan Gunung Djati Bandung, 2021)
This study aims to discuss the hadith regarding the cultivation of dates. This research method is a qualitative type through literature study and field studies with the takhrij and sharah hadith approaches. The results and discussion of this research is the cultivation of dates in terms of economics and ecology. The conclusion of this research is the takhrij and syarah hadith of the Prophet SAW, about the potency of cultivating dates which can create a new industry in Indonesia with agrotechnology analysis.